Computational Pipeline for the PGV-001 Neoantigen Vaccine Trial - Rubinsteyn, Alex; Kodysh, Julia; Hodes, Isaac; Mondet, Sebastien; Aksoy, Bulent Arman; Finnigan, John P.; Bhardwaj, Nina; Hammerbacher, Jeffrey (Frontiers in Immunology, 2018)
This paper describes the sequencing protocol and computational pipeline for the PGV-001 personalized vaccine trial. PGV-001 is a therapeutic peptide vaccine targeting neoantigens identified from patient tumor samples. Peptides are selected by a computational pipeline which identifies mutations from tumor/normal exome sequencing and ranks mutant sequences by a combination of predicted Class I MHC affinity and abundance estimated from tumor RNA. The PGV pipeline is modular and consists of independently usable tools and software libraries. We hope that the functionality of these tools may extend beyond the specifics of the PGV-001 trial and enable other research groups in their own neoantigen investigations.